2021
DOI: 10.3389/fpsyg.2021.585534
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Anxiety in Patients With Cancer: A Cross-Sectional Study

Abstract: ObjectivesDepression and anxiety persist in cancer patients, creating an additional burden during treatment and making it more challenging in terms of management and control. Studies on the prevalence of depression and anxiety among cancer patients in the Middle East are limited and include many limitations such as their small sample sizes and restriction to a specific type of cancer in specific clinical settings. This study aimed to describe the prevalence and risk factors of depression and anxiety among canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
7
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(101 citation statements)
references
References 51 publications
8
77
7
9
Order By: Relevance
“…44 On the other hand, our finding is higher than studies by Naser et al, in Jordan (23.4%). 45 This disparity might be attributed to differences in the study populations in terms of cancer types, screening tools used, or other sociodemographic variations and severity of depression taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…44 On the other hand, our finding is higher than studies by Naser et al, in Jordan (23.4%). 45 This disparity might be attributed to differences in the study populations in terms of cancer types, screening tools used, or other sociodemographic variations and severity of depression taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the immune system is distracted and goes into fright/flight mode. If this mode is temporary, it is manageable, however, if it remains permanent, the patient who started with one disease, cancer, will have a total of three diseases upon hearing the news: anxiety, depression, and cancer [26][27][28]. When chemotherapy is administered while the immune system is in distraction mode, the therapeutic outcome is limited to the therapeutic effect of the chemotherapy or other therapeutic options, while other important effects related to potential energy sources are either dispersed or suppressed.…”
Section: Patient With Cancer Diseasementioning
confidence: 99%
“…The inclusion criteria were: (a) patients aged 18 years and above with a histologically con rmed cancer diagnosis and patients who had no apparent cognitive de cit. Patients were excluded if they were unable to participate in this study due to physical or emotional distress [15]. A semi-structured questionnaire was used for data collection.…”
Section: Sample Size and Sampling Techniquementioning
confidence: 99%
“…In Babol, Iran, depression was seen among 21.3% of the cancer patients [11]. A similar study at King Hussein Cancer Center in Jordan had reported depression prevalence of 23% using the patient health questionnaire (PHQ-9) [15]. While in Pakistan, using the Aga Khan University Anxiety and Depression Scale (AKUADS) the prevalence was 48.9% [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation